Achieving climate-smart cocoa in West Africa - Bunn, Christian (International Center for Tropical Agriculture, 2019)
This document is a climate –smart cocoa profile for West Africa. It summarizes the results of a climate analysis made for the region.This brief is divided in 4 sections to guide adaptation at scale: Towards resilient production at scale, Recommendation domains to scale climate smart cocoa, Scaling climate smart cocoa, Climate smart cocoa practices.